Kesesuaian Komponen Kawasan Wisata Kampung Laweyan terhadap Aspek Revitalisasi Kawasan Wisata Cagar Budaya - Bayu Seto Aji Pramana; Kusumastuti Kusumastuti; Rufia Andisetyana Putri (Region : Jurnal Pembangunan Wilayah dan Perencanaan Partisipatif, 2017)
Solo city which is formed from a long history has a distinctive character that is on aspects of culture and history. History and culture can not be separated from the development of the city because the city is also formed from past activities that become historical value in the present. One area in the city of Solo which has a strong historical and cultural character is “Kampung Laweyan”. It makes “Kampung Laweyan” become one of the unique areas and has potential that can be developed, the potential and unique characteristics of Kampung Laweyan is as a tourist attraction that presents cultural attractions and traditions that are still thick, especially the culture and tradition of batik. But the development of science and technology, making the historical and cultural aspects of urban development is increasingly lagging behind. The existence of “Kampung Laweyan” which put forward the historical and cultural aspects in its development also increasingly degenerate, so that the vitality of this region is also declining. Therefore in 2004 the revitalization began to revitalize the area into a tourist destination. This revitalization also reviewed its suitability as the Heritage Tourism Area. This research aims to determine the level of suitability Aspects of revitalization Tourism Laweyan Heritage Area. The method used in this research is deductive through scoring technique analysis. The data used are primary data through field observation and interview and secondary data through document study. The result of the research shows that only the aspect of the activity actor has the corresponding value while the other two aspects of tourist attraction and physical facility have unsuitable value. So that the overall assessment of conformity Aspect Revitalization of Heritage Tourism Area also has unsuitable value.